Heterodera schachtii (Nematoda: Heteroderidae) associated with cabbage-cultivation systems in anatolia region of Türkiye - Akyol, Gülsüm Badel; Yüksel, Ebubekir; Elçi, Eminur; Bozbuga, Refik; Dababat, Abdelfattah A.; Imren, Mustafa; Toktay, Halil (MDPI, 2024)
Heterodera schachtii (Schmidt, 1871) (Nematoda: Heteroderidae) is one of the most widespread plant-parasitic nematodes (PPNs) associated with cabbages, which cause severe yield losses in cruciferous vegetables. This study aimed to improve the current understanding of the prevalence and detection of H. schachtii in the cabbage-growing areas of Niğde Province, Türkiye. Field surveys were conducted between November and December 2021, and 100 soil samples were collected immediately after cabbage harvesting. Heterodera schachtii populations were identified by morphological and morphometric methods along with Internal Transcribed Spacer of the ribosomal region (ITS-rDNA) and Cytochrome Oxidase Subunit (COI-mtDNA) sequencing. The mean body length of H. schachtii was 463 ± 7 μm, while stylet and hyaline length ranged between 20.7–27.8 μm and 20.1–32.1 μm, respectively. Nearly half of the surveyed areas were infested with H. schachtii with a 41% incidence rate. However, the Merkez District had the highest proportion of infested fields with an over 51% incidence rate. The population density was determined in 41 samples with a mean of 79.5 cysts per 250 g of soil. These results will help to determine the control and management strategies of H. schachtii.